FRI0265 Angiogenic t cells in primary sjÖgren's syndrome: a double-edged sword. (12th June 2018) - Alunno, A.; Manetti, M.; Bistoni, O.; Cipriani, S.; Ibba Manneschi, L.; Gerli, R.
Abstract : Background: Angiogenic T cells (Tang) have been recently identified within colonies of endothelial progenitor cells (EPCs) as mediators of endothelial repair. Both Tang and EPCs are reduced in rheumatoid arthritis and this contributes to persistent endothelial damage and eventually increased cardiovascular risk. In primary Sjögren's syndrome (pSS), EPCs are expanded but no data are currently available about Tang. Objectives: Aim of this study was to assess Tang (CD3 +CD31+CXCR4+) in peripheral blood (PB) and target organs of pSS as well as the association with EPCs (CD34 +CD133+VEGFR-2+) and clinical and serological features of the disease. Methods: Thirty-six pSS patients and 20 sex- and age-matched healthy donors (HD) were enrolled. Phenotipic analysis of peripheral blood mononuclear cells was performed by flow cytometry using FITC, Pe, Pe-Cy7 or AlexaFluor647 labelled anti-human CD3, CD31, CXCR4, CD4, CD8, CD28, CD34, CD133, VEGFR-2, and IL-17 antibodies. Minor salivary gland (MSG) biopsies from 8 pSS patients were studied and compared to samples from 12 patients with sicca symptoms and either non-specific chronic sialadenitis (NSCS) or normal parenchyma (n=6 each). MSG sections were subjected to immunofluorescence staining to assess the presence of CD3 +CD31+CXCR4+Tang cells and the expression of the CXCR4-ligand CXCL12/SDF-1 chemokine. Results: Circulating Tang were expanded in pSS compared to HD and were directly correlated to EPCs. Both Tang and EPCs directly correlated with disease activity as calculated with the EULAR Sjögren's syndrome disease activity index (ESSDAI). Over 60% of Tang lacked CD28 revealing a senescent phenotype. Only a small proportion of Tang displayed either CD4 or CD8, the majority of Tang being therefore CD4-CD8- double negative (DN). A subset of Tang produced IL-17 and the highest proportion of IL-17-producing cells was observed among DN cells. Immunofluorescence analyses revealed the exclusive presence of infiltrating Tang cells along with increased expression of CXCL12/SDF-1 in pSS MSGs compared to either NSCS or normal MSGs. Conclusions: Circulating Tang cells are expanded in pSS, display a senescent phenotype, are mainly CD4-CD8- DN and produce IL-17. Moreover, Tang cells home to and infiltrate MSGs in pSS, presumably through the SDF-1/CXCR4 chemotactic axis. Our data suggest that besides their positive effect together with EPCs in endothelial repair, Tang cells may contribute to disease pathogenesis. Disclosure of Interest: None declared